Teacher and Students' Perceptions of Interactive Digital Media Use in Arabic Language Learning in Grade VII at MTsN 2 Semarang - Hasti Dwi Handayani; Inayah; Muhammad Ahsanul Husna; Waesama-ae Waemamu (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study investigates the implementation and analyzes the perceptions of teachers and students regarding the use of interactive digital media (Canva and Wordwall) in Arabic Language Learning (ALL) for Grade VII students at MTsN 2 Semarang. This research employed an explanatory field research design using mixed methods to explore subjective experiences in a natural context without manipulation. Data were collected through questionnaires distributed to 295 students (using a five-point Likert scale), semi-structured interviews with Arabic teachers, and participatory observation. Quantitative data were analyzed descriptively with percentages, while qualitative data utilized the Miles & Huberman model (data reduction, data display, and conclusion drawing). The findings reveal that the integration of Canva and Wordwall significantly enhances student engagement and active participation in Arabic language learning. Teachers reported that these media function as effective instructional tools, particularly in strengthening receptive language skills such as reading (Qirā’ah), vocabulary acquisition, and understanding sentence structures through visual and interactive learning activities. Wordwall’s gamification features also promote student motivation and facilitate vocabulary and grammar practice. However, the impact of these digital media on productive language skills, such as speaking (Kalām) and writing (Kitābah), remains relatively limited due to their predominant use in reading and comprehension-based activities. Overall, students demonstrated highly positive perceptions, with 64% expressing agreement or strong agreement that interactive digital media increased learning interest, enhanced self-efficacy, and reduced learning anxiety (affective filter). This study concludes that interactive digital media play a crucial role in creating an engaging and emotionally supportive learning environment and are particularly effective in improving receptive language skills, especially reading comprehension and vocabulary acquisition.